Case Report: Uncommon cause of limp in the 21st century - Thiemann, Stephanie; Cimorelli, Valeria; Bajwa, Nadia M. (Frontiers in Endocrinology, 2022)
Scurvy results from a deficiency of ascorbic acid. This disease first appeared in children during the 19th century with the emergence of new dietary habits; in particular, heating milk that leads to a loss of ascorbic acid. Even though scurvy has become a rare condition in western countries, many cases are still reported in pediatric patients, especially in those who lack proper nutrition due to neurological or psychiatric illnesses. Symptoms include bleeding and swollen gums, loosening of teeth, bone abnormalities, arthralgia, delayed wound healing, anemia, petechiae, and purpura. Bone lesions are mainly irregularities of long bones metaphyses. We report the case of a five-year-old boy who presented with arthralgia and limb deformation (genu valgum). The patient was investigated for vitamin deficiencies to exclude rickets. The radiologic investigations revealed metaphyseal signs compatible with scurvy. During the hospitalization, the patient was observed to have abnormal eating patterns and the scurvy was attributed to malnutrition. Although the occurrence of scurvy is rare, it remains essential to detect this disease in children at risk of developing vitamin deficiencies. Without targeted treatment, the complications of scurvy can be serious and potentially fatal.